Preharvest treatment of ‘Gala’ apples with 1-MCP and AVG – II: Effects on fruit quality after storage - Argenta L.C. (2018)
© 2018 International Society for Horticultural Science. All rights reserved.The effects of preharvest treatment with 1-methylcyclopropene (1-MCP) in water on post-storage apple fruit quality were examined in comparison to that of aminoethoxyvinylglycine (AVG). 1-MCP (150 mg L-1) and AVG (124 mg L-1) were sprayed to ‘Imperial Gala’ and ‘Royal Gala’ apple trees, 7 and 28 days before commercial fruit harvest maturity, respectively, during four consecutive years. Untreated trees were used as control. Fruit were harvested weekly, during four weeks from the 7th day after 1-MCP spray and stored in regular air at 0.5°C for 120 days, or in controlled atmosphere (CA) at 0.7°C for 210 days, plus 7 days at 22°C. Regression analyzes for fruit quality attributes as a function of harvest date were performed to estimate post-storage firmness, soluble solids content, acidity and disorder indices for the estimated harvest dates when fruit of all three preharvest treatments achieved the same firmness of 71.1 N, at harvest. Preharvest 1-MCP and AVG treatments slowed softening and decreased severity of physiological disorders and decay associated to the delay of harvest date, depending on orchard, cultivar, and storage atmosphere. However, sprayable 1-MCP and AVG did not affect rates of fruit softening and internal browning development following air storage and did not affect or reduce rates of fruit softening and internal browning development following CA storage, if treated and untreated apple fruit were harvested at the same firmness. Sprayable 1-MCP and AVG did not reduce fruit cracking and decay following storage when fruit of these two treatments were harvested with same firmness of control fruit (71.1 N). Effects of AVG were similar to or greater than those of sprayable 1-MCP for retention of fruit firmness and reduction of internal browning following air and CA storage.